Negative governance: vulnerability, biopolitics and the origins of government. Issue 2 (26th July 2013) - Rose, Mitch
<x xml:space="preserve">Abstract</x> This paper develops the concept of negative governance, an idea that describes (1) a unique and specific modality of governance and (2) a way to think about the concept of governance in general. In terms of the former, negative governance describes a way of governing that works by refusing to govern. This refusal is not simply a denial of state provision (since this assumes a governing agent), but a denial of state management. Negative governance is a system of governing paradoxically predicated on the withdrawal of all positive procedures of state and a delegation of power to those forces that are by definition outside the state's capacities. It governs by allowing 'life itself' – life in all is chaotic unpredictability – to rule. In terms of the latter, negative governance raises questions about the origins of governance. Specifically, it asks 'what is it that calls for governance?' My answer is that the 'call to govern' emanates from a place wholly outside the state and the state's own representational logic. Expanding upon Levinas' concept of the elemental, I argue that the state is not the agent that makes subjects vulnerable. On the contrary, vulnerability is a human condition: the body demands food, our loved ones come and go, death is always present. It is this basic vulnerability that calls for governance. And government is a response to this negative condition.